S’accorder en Terre Ferme vénitienne (Castelgomberto, province de Vicence, 1595-1598) - Lucien Faggion (Criminocorpus)
For a long time, historians of law and justice have paid attention above all to the crimes committed and the judgments pronounced, and neglected the regular work accomplished by notaries, which they exercise in cities or the countryside. However, these provide important information on disagreements, disputes, and conflict resolution, which were often investigated by the city court. Therefore the study of notarial deeds recorded at the end of the 16th century by four notaries from the village Castelgomberto, located in the Venetian Terra Firma, allows us to understand how individuals resolve their disputes, what authorities are requested and to know the language of the peace.